Answer:
Solution of the given system of equations is x = 6 and y = 2
Explanation:
In the given system equations are
2x + 3y = 18 -------(1)
3x - 3y = 12 --------(2)
We add equation 1 and 2 to get the value of x
(2x + 3y) + (3x - 3y) = 18 + 12
2x + 3x + 3y - 3y = 30
5x = 30
x =
![(30)/(5)=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1ezdj1gctcjpy8ucvuj06oaq0wi5llnd26.png)
Now we put the value of x in equation 1.
2(6) + 3y = 18
12 + 3y = 18
3y = 18 - 12
3y = 6
y = 2
Therefore, solution of the given system of equations is x = 6 and y = 2